(untitled) (Eurasian Research Bulletin, 2022)
Non-alcoholic fatty liver disease (NAFLD) high prevalence, a tendency to an increase in morbidity, disease progression, coverage of the most efficient part of the population, the severity of clinical manifestations only in the late stages makes it possible to classify NAFLD as socially significant, of course, makes NAFLD one of the urgent problems of clinical medicine. The main feature of NAFLD is the absence of symptoms; the disease is often detected by chance, based on laboratory or instrumental tests. This article studied clinical and laboratory analyzes of 98 patients with non-alcoholic fatty liver disease. With steatohepatitis, higher ALT and AST values are noted than in patients with hepatic steatosis. The main differential difference between non-alcoholic steatosis and steatohepatitis, available in clinical practice, may be the severity of the biochemical syndrome of cytolysis. The article contains clinical features and prognosis in patients with fatty hepatosis and non-alcoholic steatohepatitis (NASH). Dyslipidemia (hypertriglyceridemia, decreased HDL, increased LDL) occurs in about 65-85% of patients. The basal insulin level, according to the results of our studies, in persons with NAFLD at the stage of steatosis and steatohepatitis was significantly increased